PTU-169 The Two Week wait – is it any Good at Diagnosing Oesophogo-Gastric Cancers?. (4th June 2013) - Beg, S; Deacon, J; Badiani, R; Morris, D L
Abstract : Introduction: The two week wait (2WW) for suspected upper gastrointestinal cancer was introduced by the Department of Health in 2000 to identify of those at risk of malignancy and to fast track their investigation and management. Twelve years on, we aimed to assess the value of this mode of referral and whether this alters outcomes for those diagnosed through this pathway. Methods: All patients diagnosed with oesophogastric cancer between April 2011 and March 2012 at the QEII and Lister hospitals, were retrospectively reviewed using our MDT database. These cases were analysed with respect to mode of referral, TNM stage of disease at diagnosis and subsequent management. We reviewed all upper gastro-intestinal 2WW referrals for gastroscopy in the same time period, to determine the proportion which represents malignancy in whom malignancy was found. Results: During this twelve month period 87 gastro-oesophageal cancers were diagnosed, 75% were oesophageal compared to 25% gastric in origin. There was a male preponderance, accounting for 61% of cases, the average age at diagnosis being 71 years old. 56% were diagnosed via the 2WW, whilst the remainder presented as routine referrals (19%), emergency admissions (22%) and referrals from other specialities (3%). Tumour staging (TNM) at the time of diagnosis was comparable between the routine and 2WW referrals as was the proportion of those who had advanced disease at diagnosis (T4 and above) accounting for 47% and 52% of cases respectively. When reviewing all 2WW referrals for gastroscopy the cancers pick up was 10% with the majority of examinations being normal or identifying insignificant findings. Conclusion: The two week wait referral system is often considered to be a poor method for detecting oesophagogastric cancer. In our data 10% patients referred in this manner had oesophagogastric cancer which is consistant with existing data. However when looking at all cases of of cancer diagnosed in this time period the 2WW represents the pathway for diagnosis for over half our malignancies (56%). Our cohort of patients showed similar TNM staging at the time of diagnosis irrespective whether they were refered routinely or on an urgent basis. This suggests that the 2ww is an important pathway for referral of upper gastrointestinal malignancies but unfortunately does not identify patients at earlier stage. This is probably due to the lack of symptoms in early oesophogogastric cancer and strengthens the argument for identifying patients at an earlier stage perhaps by screening or surveillance of high risk groups. Disclosure of Interest: None Declared